MAKING COOKIES WITH SUBSTITUTION OF KEPOK BANANA (Musa Paradisiaca L.) FLOUR AND MORINGA (Moringa Oliefera L.) FLOUR AS AN EFFORT TO REDUCE HYPERTENSION - Hasan, Tobianus; Sine, Juni Gressilda L (Poltekkes Kemenkes Kupang, 2024)
Hypertension is a condition in which the diastolic heartbeat is greater than 90 mmHg and the systolic circulatory strain is greater than 140 mmHg in two assessments conducted over a period of minutes in a state of adequate rest and calm. Attempts are intended to assist with food consumption plans. by subbing potassium-rich fixings that are high in potassium. Since treats are made with flour, kepok banana flour and moringa leaf flour were utilized alternative for refined fixings. To pick the impact of replacement of kepok banana flour (Musa paradisiaca L.) and moringa leaf flour (Moringa oliefera L.) on the organoleptic properties of treats. The kind of investigation methodology used is a preliminary procedure using a Completely Randomized Plan (CRD) with 4 drugs. Considering the organolpetic preliminary of treats with banana kepok flour substitution, moringa leaf flour and wheat flour from the pieces of assortment, taste, surface, and the most preferred taste was (P1: 40%, 5%, 55%). The food with the most elevated healthy benefit is P3, which has the accompanying energy content: 2,651.4 grams contain 34.3 grams of protein, 135.1 grams of fat, 357.7 grams of carbohydrates, 3527.6 mg of potassium, and 18.6 grams of fiber. There are also 135.1 grams of fat. The specialists' receptivity to treatment P1 is the most good of the four classes' typical outcomes (40%: 5% : The P3 treatment has the highest healthy benefit, with 2651.4 grams of energy, 34.3 grams of protein, 135.1 grams of fat, 357.7 grams of carbohydrates, 3527.6 mg of potassium, and 18.6 grams of fiber, while the replacement for banana flour is 40% and moringa leaf flour is 5%.